Human Collagen Prolyl 4-Hydroxylase is Activated by Ligands for its Iron Center - Vasta, James D. (Biochemistry, 2016)
Collagen is the most abundant protein in animals. The posttranslational hydroxylation of proline residues in collagen contributes greatly to its conformational stability. Deficient hydroxylation is associated with a variety of disease states, including scurvy. The hydroxylation of proline residues in collagen is catalyzed by an Fe(II)- and α-ketoglutarate-dependent dioxygenase, collagen prolyl 4-hydroxylase (CP4H). CP4H has long been known to suffer oxidative inactivation during catalysis, and the cofactor ascorbate (vitamin C) is required to reactivate the enzyme by reducing its iron center from Fe(III) to Fe(II). Herein, we report on the discovery of the first synthetic activators of CP4H. Specifically, we find that 2,2′-bipyridine-4 carboxylate and 2,2′-bipyridine-5-carboxylate serve as ligands for the iron center in human CP4H that enhance the rate of ascorbate-dependent reactivation. This new mode of CP4H activation is available to other biheteroaryl compounds but does not necessarily extend to other prolyl 4 hydroxylases. As collagen is weakened in many indications, analogous activators of CP4H could have therapeutic benefit.